Relación entre la inclusión financiera y el crecimiento económico del departamento de Loreto periodo 2009 – 2023 - Reategui Lavi, Roger Ernesto (2025)
This research analyzes the relationship between financial inclusion and economic growth in the Loreto region from 2009 to 2023. Using a quantitative, correlational approach with a non-experimental design, key variables such as formal and informal employment, access to credit, and per capita GDP were examined to understand the impact of financial inclusion in a region characterized by high levels of informality and structural limitations. The findings reveal a positive, albeit moderate, correlation between financial inclusion and economic growth, highlighting the role of alternative financial institutions, such as municipal credit unions, in providing access to credit for informal sectors. Additionally, a strong relationship was found between per capita GDP and financial inclusion, suggesting a virtuous cycle between income growth and demand for financial services. The conclusions underscore the need for policies tailored to the local context that promote both access to formal financial services and economic infrastructure development in Loreto. This study provides relevant empirical evidence to design financial inclusion strategies that foster inclusive and sustainable economic growth in the region.